2007
DOI: 10.1080/00048670701579025
|View full text |Cite
|
Sign up to set email alerts
|

Australian Schizophrenia Care and Assessment Programme: Real-World Schizophrenia: Economics

Abstract: Considerable resources are required for the provision of treatment for patients with schizophrenia. But for the majority of people in this cohort, funding assertive treatment programmes and measures to reduce hospitalization was accompanied with enhanced functioning and quality of life, as well as a reduction in long-term societal and government costs. The distribution of health-care costs is highly skewed, with a relatively small proportion of patients (39%) consuming the majority of resources (80%). Improvin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 33 publications
1
15
1
Order By: Relevance
“…However, it must be noted that the data available in the literature refer to different populations from different countries, where different treatment modalities could be applied, or different unit costs are applicable, or which include older patients than those involved in our study [6-11,13-15,51,52]. In our study, medical costs during the follow up period remained stable overall.…”
Section: Discussionmentioning
confidence: 82%
See 2 more Smart Citations
“…However, it must be noted that the data available in the literature refer to different populations from different countries, where different treatment modalities could be applied, or different unit costs are applicable, or which include older patients than those involved in our study [6-11,13-15,51,52]. In our study, medical costs during the follow up period remained stable overall.…”
Section: Discussionmentioning
confidence: 82%
“…This amounted to 16% of all admissions and 34% of all bed days related to psychiatric inpatient care [12]. Among the total direct costs, hospitalizations can account for up to 94% [6], while drugs generate lower costs (between 2 and 13%) [6,13,14]. A considerable contribution to the cost to society comes from the indirect costs (i.e., productivity losses), because of employment difficulties, high early mortality rate and patients’ families loss of productivity.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Diagnostic-related groups (DRGs) have been utilized to evaluate health care costs in Spain [7]. In Australia and Germany, Fitzgerald [8] and Schreyögg et al,[9] respectively, used DRGs to assess costs. No previous studies have used DRGs to predict health care costs.…”
Section: Introductionmentioning
confidence: 99%
“…Any economic evaluation of these new products must therefore consider not only the value of the resource savings per injection no longer required, but also the net impact upon the overall workload of mental health care staff. In Australia, it has been reported that the annual cost of schizophrenia to the public health system is $841 million [4], or approximately $17,000 per patient [4,5]; literature searches though did not identify any published estimates of the resource use and non-medication costs attributable to the administration of an antipsychotic either in Australia or internationally. The Australian Department of Health and Ageing has estimated the national average cost 'per occasion of service' in outpatient psychiatric clinics of public hospitals to be $276 [6], but these visits encompass a broader range of services including general case management and evaluation and do not include allowance for mobile outreach visits.…”
Section: Introductionmentioning
confidence: 99%